Introduction to risk and uncertainty in hydrosystem engineering - Goodarzi, Ehsan (Topics in Safety, Risk, Reliability and Quality, 2013)
Water engineers require knowledge of stochastic, frequency concepts, uncertainty analysis, risk assessment, and the processes that predict unexpected events. This book presents the basics of stochastic, risk and uncertainty analysis, and random sampling techniques in conjunction with straightforward examples which are solved step by step. In addition, appropriate Excel functions are included as an alternative to solve the examples, and two real case studies is presented in the last chapters of book.